2014
DOI: 10.1007/s11682-014-9330-z
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation as a mediator of the relationship between cortical thickness and metabolic syndrome

Abstract: Objective Metabolic Syndrome (MetS), the clustering of obesity, high blood pressure, and disordered glucose and lipid/lipoprotein metabolism within a single individual, is associated with poorer cognitive function. It has been hypothesized that cognitive impairment in MetS occurs primarily within the context of inflammation. MetS risk factors are also associated with thinning of the cerebral cortex. However, the mechanisms by which MetS and inflammation affect the brain are poorly understood. The present study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 37 publications
5
15
0
Order By: Relevance
“…While mediation analysis does not allow us to draw causal conclusions, our data suggest that the ratio of KynA to neurotoxic metabolites may play a more direct role in neuroplasticity/excitotoxicity than more general markers of inflammation such as CRP. While preliminary, our results extend previous studies that have reported associations between inflammatory markers and cortical thickness in healthy populations (Kaur et al, 2014; Krishnadas et al, 2013; Marsland et al, 2015; Piras et al, 2012). Moreover, our results also are partially consistent with those of (O’Connor et al, 2009) who showed that LPS-induced depressive behavior in mice could be abrogated using the specific IDO blocker, 1-MT, without affecting the concentrations of pro-inflammatory cytokines.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…While mediation analysis does not allow us to draw causal conclusions, our data suggest that the ratio of KynA to neurotoxic metabolites may play a more direct role in neuroplasticity/excitotoxicity than more general markers of inflammation such as CRP. While preliminary, our results extend previous studies that have reported associations between inflammatory markers and cortical thickness in healthy populations (Kaur et al, 2014; Krishnadas et al, 2013; Marsland et al, 2015; Piras et al, 2012). Moreover, our results also are partially consistent with those of (O’Connor et al, 2009) who showed that LPS-induced depressive behavior in mice could be abrogated using the specific IDO blocker, 1-MT, without affecting the concentrations of pro-inflammatory cytokines.…”
Section: Discussionsupporting
confidence: 88%
“…In healthy middle-aged adults, elevations of CRP and IL-6 were inversely associated with total cortical surface area but not cortical thickness (Marsland et al, 2015). In another study, adults between the ages of 40 and 60 years showed an inverse association between serum levels of interleukin 2 (IL-2) and thickness of the inferior frontal gyrus (Kaur et al, 2014). Similarly, in middle-aged, neurologically healthy males, CRP and intercellular adhesion molecule (ICAM-1) were associated with cortical thinning of the dorsolateral prefrontal cortex (Krishnadas et al, 2013) while transforming growth factor β (TGF-β), a cytokine with anti-inflammatory properties, was positively correlated with thickness of the rACC in young adults (Piras et al, 2012).…”
Section: Introductionmentioning
confidence: 96%
“…In line with neuropsychological reports of impaired performance on tasks that rely on frontal lobe function, Kaur et al demonstrated that thinner cortical mantle in the inferior frontal ROI was associated with number of MetS risk factors [7]. Thus, there is evidence that MetS is associated with structural brain changes and that these changes are related to number of MetS risk factors.…”
Section: Introductionmentioning
confidence: 81%
“…We made the following four hypotheses: (1) Due to the relationship between MetS and AD and evidence of structural brain abnormalities associated with MetS, it was hypothesized adults with MetS would have smaller estimates of cortical thickness in MTL structures and smaller volumes of the hippocampus relative to controls [3, 4, 9]; (2) Given previous findings showing relationship between cortical thickness and number of MetS risk factors, it was hypothesized cortical thickness in MTL and the entorhinal cortex, and hippocampal volume would be associated with the number of MetS risk factors [7]; (3) It was hypothesized cortical thickness in MTL structures and hippocampal volume would be associated with memory performance as these structures are critical to memory function [8]; and (4) Given previous evidence showing that MetS is associated with reduced entorhinal cortex [9] and other structural abnormalities [6], and evidence demonstrating relationships between MTL and memory decline, it was hypothesized that the relationship between MetS and memory performance would be mediated by structural changes in the MTL.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that inflammation could mediate the relationship between metabolic syndrome and cortical thinning 38 . Additional work to explore the contribution of inflammatory markers in the kidney dysfunction related cortical thinning is worthy of investigation.…”
Section: Discussionmentioning
confidence: 99%